Clinical features in patients with simultaneous cerebral arterial and venous lesions (with literature survey) - Chew Lee Peng; N. V. Shuleshooa (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
Nowadays, only few cases of simultaneous cerebral arterial and venous thrombosis were reported. However, there might be high probability of coexisted cerebral arterial and venous changes. It is worthy to study the reasons and frequency of these coexisted vascular changes contributing to the development of clinical pictures. We analyzed 12 cases of simultaneous cerebral and/or neck vascular changes based on vascular images and ultrasonography which were divided into 4 groups: coexistence of simultaneous arterial and venous thrombosis; venous thrombosis with arterial hypoplasia; arterial thrombosis, arteritis or dissections with venous sinus hypoplasia; coexistence of arterial and venous hypoplasia.